AAV-mediated gene-replacement therapy restores viability of BCD patient iPSC derived RPE cells and vision of Cyp4v3 knockout mice. Issue 1 (4th August 2022) - Jia, Ruixuan; Meng, Xiang; Chen, Shaohong; Zhang, Fan; Du, Juan; Liu, Xiaozhen; Yang, Liping
Abstract: Bietti crystalline corneoretinal dystrophy (BCD) is an autosomal recessive retinal degenerative disease characterized by yellow-white crystal deposits in the posterior pole, degeneration of the retinal pigment epithelium (RPE), and sclerosis of the choroid. Mutations in the cytochrome P450 4V2 gene ( CYP4V2 ) cause BCD, which is associated with lipid metabolic disruption. The use of gene-replacement therapy in BCD has been hampered by the lack of disease models. To advance CYP4V2 gene-replacement therapy, we generated BCD patient-specific induced pluripotent stem cell (iPSC)–RPE cells and Cyp4v3 knockout (KO) mice as disease models and AAV2/8-CAG-CYP4V2 as treatment vectors. We demonstrated that after adeno-associated virus (AAV)-mediated CYP4V2 gene-replacement therapy BCD–iPSC–RPE cells presented restored cell survival and reduced lipid droplets accumulation; restoration of vision in Cyp4v3 KO mice was revealed by elevated electroretinogram amplitude and ameliorated RPE degeneration. These results suggest that AAV-mediated gene-replacement therapy in BCD patients is a promising strategy.